Membrane-assisted mineral trioxide aggregate apical plug for management of traumatized immature anterior teeth: Clinical case reports - Raji Viola Solomon; Parupalli karunakar; Sevvana Sree Soumya; Puppala Siddhartha (Wolters Kluwer Medknow Publications, 2014)
Apexification using calcium hydroxide has many disadvantages, such as, it needs more time for the treatment, chance for fracture of the tooth, and incomplete calcification of the bridge. There are many alternative treatments introduced, which have gained popularity, such as, forming an apical plug using mineral trioxide aggregate (MTA), for excellent results. In cases of wide open apices, it is difficult to limit the restoration to the working length, as such situations lead to the apical extrusion of the material into the periapical region, which prevents further healing. Such conditions can be best treated with the use of a resorbable collagen membrane, which limits the restoration till the working length and prevents the extrusion of the material beyond the apex. The present case reports highlight the non-surgical management of immature teeth by using a membrane as a barrier, with an MTA apical plug, followed by crown rehabilitation.